Workshop-Based Implementation of a Web-Based Spatial Sense Assessment Application for Elementary School Teachers - Elli Kusumawati; Hidayah Ansori; Juhairiah Juhairiah; M. Zainul Arifin; Mahmud Sirri; Erfina Erfina (Universitas Lambung Mangkurat, 2026)
This community service program aimed to strengthen elementary school teachers’ competence in assessing students’ spatial sense through a web-based assessment application. Spatial sense is an important mathematical ability related to spatial reasoning and geometry learning; however, many teachers still rely on conventional assessments that do not adequately capture students’ spatial abilities. This program was implemented through a workshop involving 88 elementary school teachers from the Teacher Working Group (Kelompok Kerja Guru/ KKG) Gugus Mawar in Banjarmasin Tengah. The workshop consisted of conceptual sessions on spatial sense, training on spatial sense assessment, and hands-on practice using a web-based assessment application. Data were collected through observation, interviews, and participant questionnaires. The evaluation results indicate that 89% of participants were able to operate the application independently, while 92% reported that the application was useful for conducting spatial sense assessment in classroom settings. Participants also expressed positive perceptions regarding the practicality and efficiency of the web-based system for assessment management. These findings suggest that the workshop successfully supported teachers in adopting technology-enhanced assessment practices in elementary mathematics education.